Hubungan Antara Ketakutan Rawatan Psikologi Dengan Sikap Mendapat Bantuan Kaunseling - Loh, Poh Fang (2005)
This research was conducted to explore the relationship between fears of psychological treatment and attitude towards seeking counselling among the students. In addition, the differences in fears of psychological treatment and attitude towards seeking counselling according to sex and prior contact with counsellor was ascertained. A total of 321 respondents (93 males and 228 females) were used as the sample for this study. Pearson Correlation and T-test were used to analyse the data and to test the hypotheses formed. Results of the data analysis show that there is no significant relationship between fear of psychological treatment and attitude towards seeking counselling. There is no significant difference in attitudes towards seeking counselling between males and females. However, significant difference was found in both fear of psychological treatment between male and female students, as well as between those who had prior contact with the counsellors and those who had no prior contact with the counsellors.